Evaluation of toshiba gca-901a gamma camera performance by using a material filter (cu 0.125 mm) in tc-99m conventional imaging - Isa, Ismaliza (2004)
The effect of physical filter (Cu) on the perfonnance of gamma camera (Toshiba GCA 901A) by reducing the scattered radiation has been investigated in planar imaging with Tc .. 99m radioisotope. The copper filter consisted of sheet of thickness 0.125 mm with 57 em length and 42 em width. It was placed on the face of the collimator. The Tc-99m is used to obtain the experimental data. A symmetrical photopeak energy window (20%) has been centered at 140 ke V for collection of data. In this study, low energy parallel-hole collimators are employed. They are low energy general purpose (LEGP) and low energy high resolution (LEHR). The system's imaging ability has been investigated via the analysis of uniformity, sensitivity and spatial resolution parameters. Results are compared with copper filtered data and those obtained from without the material filter data. From the overall results, data shows an improvement in all tested parameters. In conclusion, the physical filter (Cu) used in this study may be advantageous in clinical studies.